EVALUASI MANAJEMEN PENGELOLAAN PELATIHAN KLUB OLAHRAGA ATLETIK BINAAN DISPORA PROVINSI ACEH - Zikrur Rahmat; Irfandi (Jurnal Penjaskesrek, 2018)
In general, this study aims to evaluate the management of the training of Athletic Athletics Athletics Training Club Dispora Aceh, and specifically aims to assess the extent to which the development of the management of Athletic sports clubs in each District / Sub-Dinas Dispora Aceh, in the study of this study there Sabang , Aceh Besar, Pidie Jaya, Bener Meriah, Gayo Lues, Aceh Jaya, Simeulue and Aceh Singkil. In this research the method used is qualitative research method, where only judging, see the feasibility of development management of Athletic sports club management. This research activity is divided over a period of two years. Year One is to make an evaluation design of the management management of Athletic Athletics Training club at Dispora Training in Aceh Province, including all the Dispora in every Regency / City that overshadows to foster Athletic sports activities. Year Two is to analyze the feasibility of designing the development of management evaluation of the training of Athletic Athletics Training Club Dispora in Aceh Province including all the Dispora in every Regency / City that shade to foster Athletic sports activities. The results of the research are 1) To make an evaluation plan of management management of training of athletics sport club at Dispora Athletics in Aceh Province, including all Dispora in every regency / city that overshadows to foster Athletic sports activities, 2) ISBN textbook publication, and journal international indexed, 3) intellectual property rights / copyrights, 4) Make an MoU with the local government and Dispora that exist in each Kota District. The result of the research and discussion shows that the management process of Athletic Athletic Athletic Athletic Club in Aceh is still relatively low, this is because the process of management, management, recruitment process and financing are still classified as less. Abstrak Secara umum penelitian ini bertujuan untuk mengevaluasi manajemen pengelolaan pelatihan klub olahraga Atletik Binaan Dispora Aceh, dan secara khusus bertujuan untuk menilai sejauh mana perkembangan pengelolaan klub olahraga Atletik yang ada di setiap Kabupaten/Kota dibawah Binaan Dispora Aceh, dalam kajian penelitian ini yakni Sabang, Aceh Besar, Pidie Jaya, Bener Meriah, Gayo Lues, Aceh Jaya, Simeulue dan Aceh Singkil. Dalam penelitian ini metode yang digunakan adalah metode penelitian kualitatif, dimana hanya menilai, melihat kelayakan perkembangan manajemen pengelolaan klub olahraga Atletik. Kegiatan riset ini terbagi dalam kurun waktu selama dua tahun. Tahun Pertama adalah membuat rancangan evaluasi manajemen pengelolaan pelatihan klub olahraga Atletik Binaan Dispora di Propinsi Aceh, termasuk semua Dispora yang ada di setiap Kabupaten/Kota yang menaungi untuk membina kegiatan olahraga Atletik. Tahun Kedua adalah menganalisis kelayakan perancangan perkembangan evaluasi manajemen pengelolaan pelatihan klub olahraga Atletik Binaan Dispora di Propinsi Aceh termasuk semua Dispora yang ada di setiap Kabupaten/Kota yang menaungi untuk membina kegiatan olahraga Atletik. Hasil penelitian yakni 1) Membuat suatu rancangan evaluasi manajemen pengelolaan pelatihan klub olahraga Atletik Binaan Dispora di Propinsi Aceh, termasuk semua Dispora yang ada di setiap Kabupaten/Kota yang menaungi untuk membina kegiatan olahraga Atletik, 2) Publikasi buku teks ber-ISBN, dan jurnal internasional terindeks, 3) Hak atas kekayaan intelektual/hak cipta, 4) Membuat suatu MoU dengan pihak Pemda dan Dispora yang ada disetiap Kabupaten Kota. Hasil penelitian dan pembahasannya menunjukkan bahwa proses pengelolaan klub olahraga Atlet Atletik Aceh yang ada didaerah masih tergolong minim, hal ini dikarenakan proses manajemen, pengelolaan, proses perekrutan dan pembiayaan masih juga tergolong kurang. Kata Kunci: Evaluasi, manajemen, binaan, dan atletik